Influence of pre-harvest climatic variables and natural storage durationon seed physico-chemical profile in diverse maturity groups ofrice (Oryza sativa) varieties - KUMARI, SHRUTI; CHAKRABARTY, S K; PAUL, DEBASHIS; DHARMENDER (The Indian Journal of Agricultural Sciences, 2024)
Seed storage is a critical concern for farmers and seed banks, as it can significantly impact the quality of seeds over time. Present study was carried out during rainy (kharif) season of 2020–21 at ICAR-Indian Agricultural Research Institute, New Delhi to understand the physiological and biochemical factors determining seed vigour traits in relation to maturity and storage periods in rice (Oryza sativa L.) varieties. In the freshly harvested seeds, early and mid-maturity group varieties exhibited higher germination percentage and seed vigour indices compared to late and very late maturity varieties. However, with increasing storage duration, germination percentage and vigour gradually decreased in the early and mid-maturity groups, while late and very late groups showed an increase up to 8 months of storage, followed by a decline after 12 months. Catalase activity (CAT) and Super oxide dismutase activity (SOD) remained stable across maturity groups and storage periods, while peroxidase activity (POD) varied significantly in fresh seeds but not during storage. Hydrogen peroxide activity (H2O2) and α-amylase content exhibited variations among maturity groups and storage periods. The study emphasizes the crucial role of maturity group selection in seeds, both for immediate sowing and long-term storage.